Corporate Identity in Higher Education - Losāne, Nataļja; Apele, Diāna (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2015)
The aim of the article is to study and identify the importance of corporate identity in the field of higher education in Latvia, to conduct a qualitative study which is based on evaluation of Latvia's institutions of corporate identity existence. Research method - qualitative research – analysis of public discussions, which provides more comprehensive study to understanding the problem. The study of the content reveals corporate identity components and their impact on the organization as a brand. The article contains description of the terms - brand style, corporate design, brand. All of these positions are viewable by a higher education institution as a corporate organization perspective. The study reveals the need to develop a university as the brand at the international level, to create a stable, strategically targeted, modern platform of the organization.